2014
DOI: 10.3389/fnhum.2014.00511
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity, chaos and integration: hemispheric interaction and individual differences in metaphor comprehension

Abstract: Neurotypical individuals cope flexibly with the full range of semantic relations expressed in human language, including metaphoric relations. This impressive semantic ability may be associated with distinct and flexible patterns of hemispheric interaction, including higher right hemisphere (RH) involvement for processing novel metaphors. However, this ability may be impaired in specific clinical conditions, such as Asperger syndrome (AS) and schizophrenia. The impaired semantic processing is accompanied by dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 98 publications
(158 reference statements)
6
41
0
1
Order By: Relevance
“…This intra-hemispheric activation may be required for the complex interplay between specialized and non-specialized systems in processing conventional and unconventional stimuli. These neurocognitive findings converge with a recent novel theory we have proposed in regard to semantic processing (Faust and Kenett, 2014 ): We propose that efficient semantic processing is achieved via a balance between rigid, structured semantic processing (as expressed by the specialized linguistic LH lateralized system) and more chaotic, flexible semantic processing (as expressed by the non-specialized linguistic RH lateralized system). Thus, a well-balanced interaction between specialized and non-specialized neurocognitive systems is seemingly critical for the efficient processing of all types of stimuli, and for coping with the less conventional, creative features of reality.…”
Section: Discussionsupporting
confidence: 86%
“…This intra-hemispheric activation may be required for the complex interplay between specialized and non-specialized systems in processing conventional and unconventional stimuli. These neurocognitive findings converge with a recent novel theory we have proposed in regard to semantic processing (Faust and Kenett, 2014 ): We propose that efficient semantic processing is achieved via a balance between rigid, structured semantic processing (as expressed by the specialized linguistic LH lateralized system) and more chaotic, flexible semantic processing (as expressed by the non-specialized linguistic RH lateralized system). Thus, a well-balanced interaction between specialized and non-specialized neurocognitive systems is seemingly critical for the efficient processing of all types of stimuli, and for coping with the less conventional, creative features of reality.…”
Section: Discussionsupporting
confidence: 86%
“…For example, van den Heuvel et al [] found that fluid intelligence was inversely related to characteristic path length within a whole‐brain functional network, pointing to an important role of individual differences in cognitive ability in predicting brain network efficiency. Such findings provide compelling evidence for a role of cognitive, personality, and creativity variables in shaping structural and functional brain systems [Beaty et al, ; Faust and Kenett, ; Kenett et al, ; Medaglia et al, ; Ryman et al, ; van den Heuvel et al, ]. Future research should continue to explore factors underlying variation in neurocognitive network topology.…”
Section: Discussionmentioning
confidence: 99%
“…The claim is not that an ‘Aha!’ experience always happens or only happens for hard relevance-deciding problems, or that all relevance-deciding problems involve insight. Rather, insight problems lie on the opposite of the continuum from analytic, algorithmic, code-like problems [ 39 ], and the more of a burden that is placed on relevance-deciding mechanisms in a novel signalling task, the more likely it is that participants report an ‘Aha!’ experience.…”
Section: Introductionmentioning
confidence: 99%